(untitled) (Journal of Musikot Campus, 2024)
This paper investigated the preferred learning style and learning achievement of secondary-level mathematics students across various branches of school-level mathematics, including arithmetic, algebra, and geometry. This paper also analyzed the relationship between preferred learning styles and their learning achievement in mathematics. The study used a survey questionnaire among fifty grade X students from two community schools out of ten in the Bheri Municipality of Jajarkot district. For this study, a learning style questionnaire developed by Cynthia A. Arem based on Neil Fleming’s VAK model was adopted, and students’ learning achievement was analyzed. The majority of students preferred a visual learning style, followed by kinaesthetic and auditory learning styles, when learning school-level mathematics. The students’ preferred learning styles aligned with those of arithmetic, algebra, and geometry. The result shows that there is a relationship between the students’ preferred learning style and their academic achievement. According to the study, teachers should tailor their teaching plans to their students’ learning styles in order to improve school-level mathematics performance.